Kejadian ISPA Pneumonia dan Faktor Risiko yang Meningkatkan pada Bayi dan Balita - Riyanto Riyanto; Herlina Herlina (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2021)
Introduction: Acute respiratory infection or Pneumonia is one of the causes of morbidity and mortality in children under five years old, especially in developing countries. In Indonesia, pneumonia cases are the main cause of death in children under five. Global estimates show that every hour 71 children in Indonesia contract pneumonia. Purpose: To analyze the risk factors for the occurrence of ARI Pneumonia in infants and toddlers at the Metro City Health Center in 2020. Methods: This study used a case-control study design with a retrospective approach. The research sample was infants and toddlers who visited the Puskesmas with a diagnosis of Acute respiratory infection Pneumonia or pneumonia in the working area of the Metro City Health Center. The number of samples with a ratio of 1: 1 or 46 case groups and 46 control groups. The location of the research was carried out in the working area of the Metro City Health Center. Data was collected by looking at the medical records of the case and control groups, followed by structured interviews to retrospectively look at the risk factors for the occurrence of ARI Pneumonia. Bivariate data analysis using chi-square test. Results: This study found that there was an association between exposure to cigarette smoke (OR = 8,945), exclusive breastfeeding (OR = 2,179), and vitamin A administration (OR = 2,095) with the incidence of ARI Pneumonia, while the unrelated variable was status nutrition and history of asphyxia. Conclusion: Exposure to cigarette smoke, exclusive breastfeeding, and vitamin A increased the incidence of acute respiratory infection Pneumonia in infants and toddlers. It is necessary to increase the movement of smoke-free areas in the house, in addition to offices and public places and exclusive breastfeeding, and the administration of vitamin A.AbstrakPendahuluan: ISPA Pneumonia merupakan salah satu penyebab morbiditas dan mortalitas anak berusia dibawah lima tahun terutama di negara berkembang. Di Indonesia kasus Pneumonia menjadi penyebab kematian utama pada balita. Estimasi global menunjukkan bahwa setiap satu jam ada 71 anak di Indonesia yang tertular pneumonia. Tujuan: menganalisis faktor-faktor risiko terjadinya ISPA Pneumonia pada bayi dan balita di Puskesmas kota Metro tahun 2020. Metode: Penelitian ini menggunakan rancangan studi kasus kontrol dengan pendekatan retrospektif. Sampel penelitian adalah bayi dan balita yang berkunjung ke Puskesmas dengan didiagnosis ISPA pneumonia di wilayah kerja wilayah Puskesmas kota Metro. Jumlah sampel dengan perbandingan 1 : 1 atau 46 kelompok kasus dan 46 kelompok kontrol. Lokasi penelitian dilaksanakan di wilayah kerja Puskesmas Kota Metro. Pengumpulan data dilakukan dengan melihat rekam medik kelompok kasus dan kontrol, dilanjutkan dengan wawancara terstruktur untuk melihat secara retrospektif faktor-faktor risiko terjadinya ISPA Pneumonia. Analisis data bivariat menggunakan uji chi square. Hasil: Penelitian ini memperoleh hasil ada hubungan asosiasi antara paparan asap rokok (OR = 8,945), pemberian ASI eksklusif (OR = 2,179), dan pemberian vitamin A (OR= 2,095) dengan kejadian ISPA Pneumonia, sedangkan variabel yang tidak berhubungan adalah status gizi dan riwayat asfiksia. Simpulan: Paparan asap rokok, pemberian ASI eksklusif dan pemberian vitamin A meningkatkan kejadian ISPA Pneumonia pada bayi dan balita. Perlu meningkatkan gerakan kawasan tanpa rokok (KTR) di dalam rumah, selain kantor dan tempat-tempat umum dan pemberian ASI eksklusif serta pemberian vitamin A.